Accountability and transparency in English local government: moving from ‘matching parts’ to ‘awkward couple’? - Ferry, Laurence; Eckersley, Peter; Zakaria, Zamzulaila (John Wiley & Sons Ltd, 2015)
Although excessive transparency and accountability demands can have a counterproductive effect on organisational performance (Bovens, 2005), longstanding hierarchical accountability structures to ensure financial conformance in English local government continue to endure. Interestingly however, the previously top-down regime for performance accountability in English local government has been replaced by bottom-up mechanisms such as greater transparency and a more open market for public services. Using the framework developed by Hood (2010), this paper will show how such reforms mean that transparency and accountability are moving from being ‘matching parts’ to an ‘awkward couple’, and how this has significant implications for public services.